EXOTIC SCALE DALAM LINTASAN SEJARAH - Daniel Sema (Sekolah Tinggi Theologia Abdiel, 2019)
Exotic scale (exotic or foreign scales) is a scale that is not covered by Western musical traditions that is outside the major and minor systems. The number of notes in an exotic scale can be less than one octave (for example pentatonic scale) or can be more (for example octatonic scale). Exotic scales are also used to refer to certain cultural scales, for example the Persian or Hungarian scales, or certain composer finding scales, for example whole tone scales, or scales borrowed from types of capital music, such as jazz or world music . This is because these types of music do not heed the tuning system, melodic forms and aesthetic principles of Western tradition. The exotic scales basically existed long before the birth of major and minor systems. For the composer of the twentieth century the sound of this unique exotic scale became the main attraction after more than three hundred years lost by the dominance of the major-minor (1600-1900). In fact, there is now a tendency for exotic scales to be used by musicians to show the composer's identity.